The Impact of Cash Liquidity and Financial Leverage on The Performance of Iraqi Banks: A Comparative Study Between Islamic and Conventional Banks - Tareq Saeed Al-Aaraji*, Sebyan (Journal of Economics and Administrative Sciences, 2024)
Degree of financial leverage refers to the percentage of bank assets financed through debt, which banks must employ to achieve returns and cover costs, as well as the availability of cash at maturity. Therefore, the problem of the study arises in how the indicators of leverage and cash liquidity affect the indicators of financial performance in the Iraqi banking sector. That is why the study aims to use econometrics to demonstrate the impact of leverage and cash liquidity on the financial performance indicators represented by return on assets (ROA) and net profit margin (NPM) for a sample of 38 conventional and Islamic banks for the period 2010-2022. The Dynamic Panel Data methodology was used to determine the relationship between variables, which combines time series and cross-sectional, precisely the generalized moment method (GMM). Results show that financial leverage negatively and significantly impacts ROA and NPM indicators in the total sample and Islamic and conventional banks, except for the positive relationship with ROA in conventional banks. The results also showed the positive impact of cash liquidity on ROA and NPM indicators in the total sample and Islamic and conventional banks, except for its negative impact on ROA indicators in conventional banks. The results also showed the negative impact of the cash credit (cash credit to total assets ratio) on ROA and NPM indicators in the total sample and Islamic and conventional banks. Paper type: Research paper